Stiffness and damping model of bolted joints with uneven surface contact pressure distribution - Zhao, Yongsheng (Strojniški vestnik, 2016)
Bolted connections are widely employed to fix the structural components, in which the bolted joint is one of the weakest parts and can significantly affect the dynamic characteristics of the machine tool. In this research, a stiffness and damping model based on the uneven surface contact pressure is presented for the bolted joint to accurately predict the dynamic characteristic of a bolted assembly. The normal and tangential stiffness and damping of the contact surface can be deduced based on the fractal contact theory. However, the contact surface pressure of bolted joint is unevenly distributed due to the influence of the concentrated force of multi-bolts. Therefore, the pressure of the contact surface is introduced to define the stiffness and damping of bolted joint. The assumption is that the contact surface is flat in the macro-scale. Then, we can obtain the pressure distribution of contact surface through the finite element (FE) method. The nonlinear relationship of stiffness, the damping of the bolted joint, and the pressure of contact surface can be obtained and assigned to the FE model based on the pressure distribution of the contact surface. An experimental set-up with a box-shaped specimen is designed for validating the proposed model. The equal pre-tightening force and bending moment effect case studies are provided to demonstrate the effectiveness of the model. The results show that the proposed model can be used to accurately predict the dynamic characteristic of the machine tool.
Keywords: dušenje; kontaktna togost; neenakomerna porazdelitev pritiska; obdelovalni stroji; teorija fraktalnega kontakta; vijačne zveze